CALCULATION OF THE WEAR OF CONTACT FRICTION PAIR STOCK − GUIDE HYDRAULIC DAMPER WITH USING THE MODERN COMPUTER MODELING METHODS (Transport systems and technologies, 2018)
The article presents a description of the most common faults of components of the hydraulic damper of oscillations of type НЦ-1100, which lead to the loss of its operable state. In the conditions of the passenger wagon depot on the bench equipment, the effect of the wear of the guide on the operation of the hydraulic damper of vibrations is investigated, the results of the work on determining the contact forces of the frictional friction pair «rod-guide» of the hydraulic shock absorber НЦ-1100 of a typical and improved passenger car are described.In the software package SolidWorks Motion, the robots of the mechanism are modeled taking into account the dynamic loads from the car body to the power elements of the damping device. The distribution of contact forces in the friction zone of the responsible rod-guide pair and the effect of lateral horizontal forces, which are transmitted to the shock-absorber attachment points, are established.
Keywords: hydraulic dampers, a computer model damper, working condition, modern-ization of units, wear.